Effects of different techniques of motor simulation in motor sequence memory for climbers - Wang, Joyce Jia Yin (Nanyang Technological University, 2022)
Introduction: Climbers need to execute movements sequentially to complete a climb. The perceptual cognitive ability of motor sequence memory [MSM] (i.e. memory of sequential actions) becomes crucial for performance. Motor simulation [MS] (i.e. imagery) has been recognised in sport performance and was proposed to help MSM in rock climbing. Purpose: This study examines the effect of 3 MS techniques (Internal Visual, External Visual and Kinaesthetic Imagery; I-VI, E-VI, KI) on MSM for advanced to elite climbers. Methods: I-VI (n=8, M = 24.88, SD = 3.137), E-VI (n=8, M= 26.88, SD = 1.458), and KI (n=8, M=26.75, SD = 1.753) of advanced to elite climbers (Climbing ability measured by Vermin Grading, M = 5.75, SD = 1.726) were formed using the Movement Imagery Questionnaire-3. Conducted over Zoom, participants memorised the hand sequences of 3 boulder routes (V5-V7) using the identified MS before testing MSM. Results: Kruskal-Wallis and a separate linear regression [SLR] model were applied. Kruskal-Wallis output showed no significance between the 3 MS and MSM (H(2) = 0.363, p>0.05). The SLR output showed significance in the process of E-VI on MSM, F (1,6) = 11.722, p<0.05, with a high positive correlation, r = 0.813. Conclusions: Findings support MS studies on the function of E-VI and indicate that higher variations of E-VI have effects on MSM in rock climbing even with online viewing. Climbers may hone E-VI to improve MSM for climbing performance. More studies are needed since research is in infancy. Keywords: motor simulation, motor sequence memory, rock climbers